Colonialidade do espaço e espiralidade em Ponciá Vicêncio (2003), de Conceição Evaristo - Conceição, Francis Willams Brito da (2021)
In this research, we conducted a study of "space" as a category in the novel Ponciá Vicêncio (2003), by the Brazilian writer Conceição Evaristo, considering the trajectory of Ponciá and your family, their displacement here approached from the perspective of postcolonial/decolonial and feminist studies. Initially, we develop a critical analysis of the narrative taking into account the category of space, through theoretical contributions of Antônio Dimas (1987), Juliana Morais (2016) and Luís Alberto Brandão (2013); then, we approached the elements of spatial configuration as constituents of a modern colonial state in Evaristian fiction, emphasizing concepts such as movement and regulation of territory by marks of difference, departing from discussions by Doreen Massey (2008), Gayatri Spivak (2019), Homi Bhabha (1998), Paul Gilroy (2012), and others. In a second moment of our research, we articulated the idea of a "coloniality of space", a central conceptual formulation in this research, based on the readings of Aníbal Quijano (2005), Édouard Glissant (1989), María Lugones (2019), and Walter Mignolo (2017). This allows us to infer that the characters are in a context of displacement in respect to their historical experience of origin, and, whether in the rural or urban areas, without prejudice to a dichotomous apprehension of the scenarios through which they move, there is the continuity of colonial logic, in which oppressive mechanisms such as racism, sexism, and spatial separatism are employed. Thus, based on voices that keep echoing in black feminism and the theory of intersectionality – such as bell hooks (2019), Grada Kilomba (2019) and Lélia Gonzalez (2019) – we establish the following results: the narrative is permeated by a spiral space, according to Fernanda Miranda (2019) and Leda Maria Martins (2003); and the protagonist, in a condition of displacement, performs a trajectory of movement, return and reinvention to inscribe a new cartography of possibilities for existence/resistance, which takes place, according to Leda Martins (2003, p. 65) and Spivak (2019, p. 268), through the strategy of "consignment of space" and the process of "remaking history". Thus, this dissertation research allowed us to reach the following results: the protagonist and her family meet in a space regulated by coloniality, and use performance – such as the comings and goings in time-space, the emptiness, the feelings of absence and abortions – aiming to break with the continuity of colonial control, and spirality, therefore, is a foundation, which expresses both the intermites of power oppressions and the repetitions of the insurgency performances of the characters.